Different Extra-coronal Restoration Options Of Hemisected Teeth On Structurally Compromised Mandibular Molar: Report Of Two Cases. - Sobrina Mohamed Khazin; Siti Hajar Omar (IIUM, 2024)
IIUM Journal of Orofacial and Health Sciences Volume 4 Issue 1 Page (89-98)